Long-term outcome of surgical excision of leukoplakia in a screening intervention trial, Kerala, India - Gigi Thomas; Ramadas Kunnambath; Thara Somanathan; Babu Mathew; Manoj Pandey; Sankaranarayanan Rangaswamy (Wolters Kluwer Medknow Publications, 2012)
Oral cancer is often preceeded by precancerous lesions and conditions, such as leukoplakia, erythroplakia and oral submucous fibrosis. One of the approaches for control of oral cancer is to detect oral precancerous lesions early in the development and prevent their malignant transformation to invasive cancer either by chemoprevention or by surgical excision of the lesions with concurrent control of tobacco and alcohol use and other specific etiological factors. However, the value of specific approaches, such as surgery in long-term control of lesions and prevention of malignant transformation is not known. We describe our experience with cold knife surgical excision of oral leukoplakia diagnosed in the context of a community-based oral cancer cluster randomized oral cancer screening trial in Kerala, jointly organized by the Regional Cancer Centre, Trivandrum and the International Agency for Research on Cancer of the WHO, Lyon. France. During the period from January 1997 to December 2002, 111 subjects underwent surgical excision- Thirteen patients were found to have malignancy on histopathology and were not considered for further analysis. At the last follow-up, 9 (13%) patients could not be traced and 19 (27%) patients died due to causes other than oral cancer. Of the remaining 70 cases, 48 (68-6%) were remaining disease free with no evidence of recurrence or new lesions, 16 (16.9%) developed new leukoplakic lesions, (one patient developed recurrence as well), three (4.2%) developed recurrence. Recurrence was more common among those who continued the habits, but this was not statistically significant. There were four (5 7%) cases of malignant transformation during the mean follow-up period of 8-1 years. The superiority of surgical excision over other modalities of management of leukoplakia could not be established in the present study.